KAJIAN PENERAPAN PENDEKATAN INKUIRI DAN PEMANFAATAN POTENSI LOKAL PADA RPP BUATAN GURU IPA (BIOLOGI) SMP KOTA TARAKAN - Ibrahim Ibrahim; Endik Deni Nugroho (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2020)
Abstract: This study wants to reveal how far the teacher has developed the lesson plan for biology learning with an inquiry approach and the use of local potentials available in the biology learning process. This type of research is a descriptive study with a qualitative approach. Sources of data in this study are lesson plans made by science teachers (Biology) SMP and opinion poll questionnaire studies. The target schools are SMPN 1, SMPN3, SMPN6, MTSN, SMPN 2, SMP Frater Don Bosco. The instruments and data analysis used to obtain the main data in this study were in the form of a lesson plan analysis rubric which was also supported by a teacher opinion survey questionnaire. The results of the study on the application of the inquiry approach, the mean percentage of all aspects of TP, MP and family planning from 134 lesson plans compiled by science (Biology) teachers of SMP Tarakan from 6 schools were found to be 51.7% bearing the title of less. In the aspect of learning objectives (TP) in the IPA (Biology) lesson plan made by Tarakan City Middle School teachers, the percentage was 17.4% with very poor category. In the aspect of the learning method in the Science (Biology) lesson plan made by Tarakan City Middle School teachers, the percentage was 64.2% with the sufficient category. Whereas in the aspect of the aspect of learning activities in the Biology lesson plan made by Tarakan City Middle School teachers, the percentage was 73.4% in the good category. In the aspect of utilizing the potential of schools / locations, it is still limited, only near the school environment. Only a few schools, such as SMPN 1 and SMPN 6, take advantage of local potential outside of school. Keywords: Inquiry Approach, Local Potential, Science Teacher, Lesson Plan